Brainstem tumor as a cause of headache triggered by Valsalva maneuver - Valença, Marcelo Moraes; Valença, Martina Falcão; Andrade, Juliana Ramos; Ribeiro, Elayne Cristina de Oliveira; Bem Junior, Luiz Severo; Silva, Ana Cristina Veiga; Mota, Rita de Cássia Ferreira Valença; Silva , Ubiratan Alves Viturino da; Angelo Júnior, José Ronaldo Lessa (Headache Medicine, 2021)
Expansive lesions of the posterior fossa or the malformation in the occipitocervical transition can cause headache triggered by Valsalva maneuver, usually of sudden onset and of significant intensity, which usually lasts for a short time. Brainstem tumor is rarely related to cause headache, hence the interest in documenting this patient's case in this article.